2006
DOI: 10.1586/14789450.3.4.399
|View full text |Cite
|
Sign up to set email alerts
|

Photoaffinity labeling combined with mass spectrometric approaches as a tool for structural proteomics

Abstract: Protein chemistry, such as crosslinking and photoaffinity labeling, in combination with modern mass spectrometric techniques, can provide information regarding protein-protein interactions beyond that normally obtained from protein identification and characterization studies. While protein crosslinking can make tertiary and quaternary protein structure information available, photoaffinity labeling can be used to obtain structural data about ligand-protein interaction sites, such as oligonucleotide-protein, dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 47 publications
0
63
0
2
Order By: Relevance
“…2B (lower panel). To narrow down the list of candidates for further study, bands were prioritized that showed Ͼ2-fold reduction in 32 P signal intensity when the PAL reaction was performed in the presence of NAADP (10 M). From this analysis, it was evident that four bands, at ϳ250 kDa (band 1), ϳ102 kDa (band 2), ϳ27 kDa (band 8), and a doublet at 22/23 kDa (band 9), met this criterion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2B (lower panel). To narrow down the list of candidates for further study, bands were prioritized that showed Ͼ2-fold reduction in 32 P signal intensity when the PAL reaction was performed in the presence of NAADP (10 M). From this analysis, it was evident that four bands, at ϳ250 kDa (band 1), ϳ102 kDa (band 2), ϳ27 kDa (band 8), and a doublet at 22/23 kDa (band 9), met this criterion.…”
Section: Resultsmentioning
confidence: 99%
“…For resolution of the 32 P signal, air-dried gels were exposed on phosphor screens (Packard Instrument Co.) at room temperature or on extra-sensitive x-ray film (Thermo Scientific) for 24 -96 h at Ϫ80°C. Quantification of 32 P signals was performed densitometrically using OptiQuant software (Version 3.0, Packard Instrument Co.). Curve fitting and statistical analyses were performed using GraphPad Prism (GraphPad Software Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…With advances in MS instrumentation and computational analysis of the MS data, it became possible to precisely determine the residues involved in the crosslink (3)(4)(5). Crosslinks provide constraints on the through-space distance of the attachment sites, and this information can aid structure prediction (6,7), can distinguish protein conformations (8), and can identify the interaction surface between proteins (9,10) and between proteins and their ligands (11). Crosslinking-MS-based methods are widely applicable as they only require microgram quantities of protein, are not limited by protein size or solubility and are relatively tolerant against sample heterogeneity.…”
mentioning
confidence: 99%
“…Crosslinking reagents are used extensively and in combination with MS, are a very powerful tool. 1,[94][95][96] High throughput screens provide an excellent start point for determining what cohort of proteins interact with the test protein and in combination with bioinformatics and computational tools they will allow the researcher to predict with a high degree of certainty what signaling pathways the test protein is involved in. It is essential then to move to a series of validation systems to confirm an interaction and also to identify the binding interface between the two proteins.…”
Section: 97mentioning
confidence: 99%